Hoxa9 and Hoxa10 induce CML myeloid blast crisis development through activation of Myb expression - Negi, Vijay (Oncotarget, 2017)
Mechanisms underlying the progression of Chronic Myeloid Leukemia (CML) from chronic phase to myeloid blast crisis are poorly understood. Our previous studies have suggested that overexpression of SETBP1 can drive this progression by conferring unlimited self-renewal capability to granulocyte macrophage progenitors (GMPs). Here we show that overexpression of Hoxa9 or Hoxa10, both transcriptional targets of Setbp1, is also sufficient to induce self-renewal of primary myeloid progenitors, causing their immortalization in culture. More importantly, both are able to cooperate with BCR/ABL to consistently induce transformation of mouse GMPs and development of aggressive leukemias resembling CML myeloid blast crisis, suggesting that either gene can drive CML progression by promoting the self-renewal of GMPs. We further identify Myb as a common critical target for Hoxa9 and Hoxa10 in inducing self-renewal of myeloid progenitors as Myb knockdown significantly reduced colony-forming potential of myeloid progenitors immortalized by the expression of either gene. Interestingly, Myb is also capable of immortalizing primary myeloid progenitors in culture and cooperating with BCR/ABL to induce leukemic transformation of mouse GMPs. Significantly increased levels of MYB transcript also were detected in all human CML blast crisis samples examined over chronic phase samples, further suggesting the possibility that MYB overexpression may play a prevalent role in driving human CML myeloid blast crisis development. In summary, our results identify overexpression of HOXA9, HOXA10, and MYB as critical drivers of CML progression, and suggest MYB as a key therapeutic target for inhibiting the self-renewal of leukemia-initiating cells in CML myeloid blast crisis patients.